MODEL PEMBELAJARAN RASULULLAH SAW DALAM PERSPEKTIF PSIKOLOGI - Aprin Nuur Faaizun (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2014)
Worsening of religious values in the daily life of Muslims resulted in an identity crisis and do not know his guidance. Especially for adolescents who are going through a search for identity. This identity crisis makes the guidelines on what is most close to the teens to be chosen, while education has been given to addressing the issue has not fully sunk in adolescent life. However, models of learning undertaken by the Prophet Muhammad proved to be effective for alleviating the problems of the people in the days of ancient ignorance, first he did not rule out the psychological aspects in each learning. This study aims to determine the learning model of the Prophet Muhammad and knowing psychological perspective of the learning model of the Prophet Muhammad. This research included in this type of research literature. Data analysis was carried out by performing data reduction, examine the data, verify the data, then be deduced. Results of the study: (1) learning model Prophet loaded with active learning, innovative, creative, effective and fun, (2) psychological perspective of the Prophet learning model can be seen from the learning theories of educational psychology.